Plasma D-Dimer Is Noninferior to Serum C-Reactive Protein in the Diagnosis of Periprosthetic Joint Infection. (5th April 2023) - Tarabichi, Saad; Goh, Graham S.; Baker, Colin M.; Chisari, Emanuele; Shahi, Alisina; Parvizi, Javad
Abstract : Background: No single test has demonstrated absolute accuracy in the diagnosis of periprosthetic joint infection (PJI). Serological markers are often used as screening tools in the workup of patients with suspected PJI. This study aimed to determine the diagnostic utility of plasma D-dimer for PJI in a variety of clinical scenarios. Methods: This prospective study enrolled 502 patients undergoing revision hip or knee arthroplasty. PJI was defined per a modified version of the 2018 International Consensus Meeting (ICM) criteria. Plasma D-dimer, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and fibrinogen were measured preoperatively. Receiver operating characteristic curves were used to assess the utility of each biomarker in the diagnosis of PJI. Pairwise comparison with Bonferroni correction was performed to determine whether the differences in areas under the curve (AUCs) between the markers were significant. Results: Of the 412 patients included, 317 (76.9%) did not have an infection (aseptic group) and 95 (23.1%) had an infection (PJI group). All 4 serological markers, D-dimer (AUC, 0.860; sensitivity, 81.3%; specificity, 81.7%), CRP (AUC, 0.862; sensitivity, 90.4%; specificity, 70.0%), ESR (AUC, 0.833; sensitivity, 73.9%; specificity, 85.2%), and fibrinogen (AUC, 0.798; sensitivity, 74.7%; specificity, 75.4%), demonstrated comparable accuracy for the diagnosis of PJI (all p > 0.05). When examining the performance of the different inflammatory markers in diagnosing infection caused by indolent organisms, D-dimer demonstrated the highest sensitivity at 93.8%. Conclusions: We found that plasma D-dimer was noninferior to serum CRP and ESR in the diagnosis of PJI and may be a useful adjunct when screening patients undergoing revision total joint arthroplasty. Level of Evidence: Diagnostic Level II . See Instructions for Authors for a complete description of levels of evidence.